Psychology Of Da’wah Impact On Balanced Personality Among Private Young Adult Higher University In Malaysia - Saleha Idris; Muhammad Khairi Mahyuddin; Othman Ab. Rahman; Mohd Rushdan Mohd Jailani (USIM Press, 2024)
Vol. 25 No. 1 (2021): Journal of Islamic Social Sciences and Humanities